كيفية علاج مخاطر التمويل الإسلامي - كرتات، رقية محمد محمد أحمد Kartat, Ruqaya Mohamed Mohamed Ahmed (جامعة عدن - كلية الاقتصاد والعلوم الإدارية, 2018)
تمثلت مشكلة البحث في إن المنتجات المالية الإسلامية ذات العلاقة بإدارة المخاطر تعاني قصوراً لا يتوافق مع حجم سوق الصناعة المالية الإسلامية. وجاءت أهمية البحث من الأهمية الكبيرة للتمويل الإسلامي في ظل الاتجاهات العالمية لإدارة المخاطر التي تواجه التمويل في البلاد العربية والإسلامية وفي أوروبا وكذلك أهميته كمصدر بديل وفعال. وهدف البحث إلى التعرف على مخاطر التمويل الإسلامي وإيجاد الحلول المناسبة لمشاكل التمويل الإسلامي. وتمثلت أهم نتائج البحث في تزايد الديون المتعثرة بسبب استخدام صيغ التمويل الإسلامية. لم يثبت صحته. وأوصى البحث بإنشاء قسم متخصص بالمصارف الإسلامية لإدارة المخاطر فيها وتقديم الحلول والدراسات العملية لمواجهتها طبقاً لأحكام الشريعة الإسلامية والعمل على تقليل المخاطر الداخلية.
The problem of research: The Islamic financial products related to risk management suffer from a deficiency that is not compatible with the size of the Islamic financial industry. The importance of research stems from the great importance of Islamic finance under the global trends of risk management facing financing in Arab and Islamic countries and in Europe as well as its importance as an alternative and effective source. Research Objectives: The study aims to -Identify the risks of Islamic finance and find appropriate solutions to the problems of Islamic finance. Results: By testing the hypotheses of the study, the following results were obtained -The increase in bad debts due to the use of Islamic financing formulas is incorrect. Recommendations: -The establishment of a specialized department of Islamic banks to manage risks and provide solutions and practical studies to address them in accordance with the provisions of Islamic law and work to reduce internal risks.
Keywords: الاقتصاد الإسلامي -- التمويل الإسلامي -- إدارة المخاطر -- الصيرفة الإسلامية